To formalize or not to formalize: Entrepreneurship and pro-market institutions - Dau, Luis Alfonso; Cuervo-Cazurra, Alvaro (Journal of Business Venturing, 2014)
In this paper, we examine the effects of pro-market institutions on both formal and informal entrepreneurship. While formal entrepreneurship has long been studied in economic literature, informal entrepreneurship has been less frequently discussed. The purpose of this paper, therefore, is not only to examine the impact of pro-market institutions, but also to foster a better understanding of, and introduce a method to measure, informal entrepreneurship. For the purpose of this paper, pro-market institutions are broken into their two main components: economic liberalization and governance levels. The arguments posit that economic liberalization positively impacts both formal and informal entrepreneurship while governance levels have a positive impact on formal entrepreneurship but a negative effect on informal entrepreneurship. Furthermore, governance levels reduce informal entrepreneurship to a greater extent than they increase formal entrepreneurship, resulting in a net reduction in entrepreneurial activity. The analyses of a panel covering 51 countries from 2002–2009 provide robust support for these arguments.